Dynamic impact of temporal context of Ca(2+) signals on inhibitory synaptic plasticity - Kawaguchi, Shin-ya (Nature Publishing Group, 2011)
Neuronal activity-dependent synaptic plasticity, a basis for learning and memory, is tightly correlated with the pattern of increase in intracellular Ca(2+) concentration ([Ca(2+)](i)). Here, using combined application of electrophysiological experiments and systems biological simulation, we show that such a correlation dynamically changes depending on the context of [Ca(2+)](i) increase. In a cerebellar Purkinje cell, long-term potentiation of inhibitory GABA(A) receptor responsiveness (called rebound potentiation; RP) was induced by [Ca(2+)](i) increase in a temporally integrative manner through sustained activation of Ca(2+)/calmodulin-dependent protein kinase II (CaMKII). However, the RP establishment was canceled by coupling of two patterns of RP-inducing [Ca(2+)](i) increase depending on the temporal sequence. Negative feedback signaling by phospho-Thr305/306 CaMKII detected the [Ca(2+)](i) context, and assisted the feedforward inhibition of CaMKII through PDE1, resulting in the RP impairment. The [Ca(2+)](i) context-dependent dynamic regulation of synaptic plasticity might contribute to the temporal refinement of information flow in neuronal networks.